Molecular Dynamics Studies of Monoclonal Antibody SM3 with a Peptide Antigen - Moris, Matt (My University, 2010)
MUC1 mucin protein is naturally expressed on the surface of epithelial cells in humans; it is found on the apical surface of ductal epithelia tissues. MUC1 mucin is also expressed in cancer cells in the breast, pancreas, and ovaries. Tumor mucin is immogenic and different in the glycogen structure. The antibody against the MUC1 tumor mucin, known as monoclonal antibody SM3 is made up of two large subunits (211 and 212 residues); its crystal structure complexed with the antigenic peptide ligand TSAPDTRPAPGST is known. Dynamic studies of the SM3 complexed with the antigenic peptide antigen, using VMD and NAMD, have shown hydrophobic interactions between the ligand and the aromatic rings of the protein. The purpose of this study is to determine which residues of the antigen and antibody SM3 are responsible for binding and to predict what types of attractive forces are responsible for binding in order to determine the type of alternate ligands to place in the binding pocket.
Dynamic Studies of Monoclonal Antibody SM3 with a Peptide Antigen
Color poster with text and images.
Keywords: Monoclonal antibodies; Antigens; Peptides--Immunology; Posters